How effective are advertising bans? On the demand for quality in two-sided media markets - Tanja Greiner; Marco Sahm (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study a two-sided markets model of two competing television stations that offer content of differentiated quality to ad-averse consumers and advertising space to firms. As all consumers prefer high over low quality content, competition for viewers is vertical. By contrast, competition for advertisers is horizontal, taking into account the firms' targeted advertising motive. We analyze the impact of both the strength of mutual externalities and advertisement regulation policies on the viewers' equilibrium demand for high quality content. We find that, although consumers dislike advertisements, an advertising ban in the high quality medium reduces its viewer market share and thereby the equilibrium reception of high quality content.
Keywords: D21; L13; L51; L82; 330; horizontal and vertical product differentiation; two-sided externalities; advertising ban; Fernsehwerbung; Werbebeschränkung; Wirkungsanalyse; Fernsehprogramm; Produktdifferenzierung; Dienstleistungsqualität; Externer Effekt; Theorie